Răspuns :
[tex]Modul~1:(a*9)+8*6(48)=93 \\ \\ a*9=93-48=45 \\ \\ a=45/9=5 \\ \\ \\ Modul~2:a*9=b \\ \\ b+8*6(48)=93 \\ \\ b=93-48=45 \\ \\ a=45/9=5[/tex]
1)
(a × 9) + 8×6 = 93
(a × 9) + 48 = 93
(a × 9) = 93 - 48
a × 9 = 45
a = 45 : 9
a = 5
2)
(a × 9) + 8× 6 = 93
notam (a×9) = X
X + 48 = 93
X = 93 - 48
X = 45
a×9 = 45 |:9
a = 5
(a × 9) + 8×6 = 93
(a × 9) + 48 = 93
(a × 9) = 93 - 48
a × 9 = 45
a = 45 : 9
a = 5
2)
(a × 9) + 8× 6 = 93
notam (a×9) = X
X + 48 = 93
X = 93 - 48
X = 45
a×9 = 45 |:9
a = 5